ESTIMATION OF TWO COMPONENT PARALLEL SYSTEM RELIABILITY STRESS â STRENGTH USING LOMAX DISTRIBUTION - S. Karam, Nada; M. Ali, Hadeel (MAGISTRA, 2014)
This article deals with estimations of system Reliability for two component parallel stress-strength system model with non-identical component parallel which are subjected to a common stress, using Lomax distribution with unknown shape parameters and common known scale parameter. Based on simulate, comparison studies are made between the ML, PC and MO estimators of the system reliability function.